A murder in Hollywood - Crichton, Michael, 1942-2008 (Blackstone Publishing, 2026)
A writer of the next Western blockbuster, Bloodrock, has been found dead in his motel bathtub in Hollywood. Harlow Perkins, a ruthless and brilliant investigator, takes on the case, trying to unravel the dark secrets of cast and crew to figure out the identity of the murderer.